2014
DOI: 10.5755/j01.eee.20.9.8713
|View full text |Cite
|
Sign up to set email alerts
|

Web Services Based Hybrid Recognizer of Lithuanian Voice Commands

Abstract: This paper presents the recently developed medical-pharmaceutical informative system with voice user interface. This is the first computerized system oriented towards healthcare services and industry where Lithuanian voice commands are used as a primary mean for control. Another essential property of the developed system is its hybrid nature: two different recognizers -an adapted commercial Spanish speech recognizer available from Microsoft and a locally developed HMM speech recognizer based on Lithuanian acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This study is the continuation of our earlier research. In [8] we showed that Microsoft SAPI could be applied to recognize Lithuanian voice commands. In [4] method to select transcriptions to recognize Lithuanian commands using foreign language speech engine was shown.…”
Section: Accuracymentioning
confidence: 99%
“…This study is the continuation of our earlier research. In [8] we showed that Microsoft SAPI could be applied to recognize Lithuanian voice commands. In [4] method to select transcriptions to recognize Lithuanian commands using foreign language speech engine was shown.…”
Section: Accuracymentioning
confidence: 99%
“…At the same time it has been shown that proper adaptation of existing foreign language acoustic models could speed up the development of recognizer and lead to the acceptable recognition level in that language [1]- [4], [6], [7]. Some previous studies have shown that speech recognition systems of languages such as English, Spanish or Russian can be quite well adapted for Lithuanian speech recognition [1], [3], [4]. However, the recognition results are not always as good as necessary and depend on many factors.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, researchers are experimenting with different acoustic models adaptation methods in order to maximize the recognition performance with small amount of non-native data available [11]. Statistical algorithms for combining different acoustic models are used quite often and produces promising results [1], [3], [4], [6], [11], [12]. These researches shows, that in many cases it is possible to achieve high enough recognition accuracy by using hybrid systems with adapted acoustic models.…”
Section: Introductionmentioning
confidence: 99%